The Alexandria link : a novel - Berry, Steve, 1955- (New York : Ballantine Books, 2007)
"Too bad former secret agent Cotton Malone knows how to unearth the lost contents of the Library of Alexandria; now his bookstore has been ransacked and his son kidnapped."--From source other than the Library of Congress
ADVENTURE
1
Keywords: Alexandrian Library -- Fiction; Malone, Cotton (Fictitious character) -- Fiction; Booksellers and bookselling -- Fiction; Antiquarian booksellers -- Fiction; Kidnapping -- Fiction; Suspense fiction